Automated Spatial Brain Normalization and Hindbrain White Matter Reference Tissue Give Improved [18F]-Florbetaben PET Quantitation in Alzheimer's Model Mice - Overhoff, Felix; Brendel, Matthias; Jaworska, Anna; Korzhova, Viktoria; Delker, Andreas; Probst, Federico; Focke, Carola; Gildehaus, Franz-Josef; Carlsen, Janette; Baumann, Karlheinz; Haass, Christian; Bartenstein, Peter; et al. (Frontiers in Neuroscience, 2016)
Preclinical PET studies of β-amyloid (Aβ) accumulation are of growing importance, but comparisons between research sites require standardized and optimized methods for quantitation. Therefore we aimed to evaluate systematically the 1) impact of an automated algorithm for spatial brain normalization, and 2) intensity scaling methods of different reference regions for Aβ-PET in a large dataset of transgenic mice. PS2APP mice in a six week longitudinal setting (N = 37) and another set of PS2APP mice at a histologically assessed narrow range of Aβ burden (N = 40) were investigated by [18F]-florbetaben PET. Manual spatial normalization by three readers at different training levels was performed prior to application of an automated brain spatial normalization and inter-reader agreement was assessed by Fleiss Kappa (κ). For this method the impact of templates at different pathology stages was investigated. Four different reference regions on brain uptake normalization were used to calculate frontal cortical standardized uptake value ratios (SUVRCTX/REF), relative to raw SUVCTX. Results were compared on the basis of longitudinal stability (Cohen’s d), and in reference to gold standard histopathological quantitation (Pearson’s R). Application of an automated brain spatial normalization resulted in nearly perfect agreement (all κ ≥ 0.99) between different readers, with constant or improved correlation with histology. Templates based on inappropriate pathology stage resulted in up to 2.9% systematic bias for SUVRCTX/REF. All SUVRCTX/REF methods performed better than SUVCTX both with regard to longitudinal stability (d ≥ 1.21 vs. d = 0.23) and histological gold standard agreement (R ≥ 0.66 vs. R ≥ 0.31). Voxel-wise analysis suggested a physiologically implausible longitudinal decrease of global mean scaling. The hindbrain white matter reference (Rmean = 0.75) was slightly superior to the brainstem (Rmean = 0.74) and the cerebellum (Rmean = 0.73). Automated brain normalization with reference region templates presents an excellent method to avoid the inter-reader variability in preclinical Aβ-PET scans. Intracerebral reference regions lacking Aβ pathology serve for precise longitudinal in vivo quantification of [18F]-florbetaben PET. Hindbrain white matter reference performed best when considering the composite of quality criteria.